IGM damping wing constraints on the tail end of reionization from the enlarged XQR-30 sample - Greig, Bradley; Mesinger, A; Bañados Torres, Eduardo; Becker, G D; Bosman, Sarah; Chen, H; Davies, Frederick B.; D’Odorico, V; Eilers, A -C; Gallerani, S; Haehnelt, M G; Keating, L; et al. (Monthly notices of the Royal Astronomical Society, 2024)
The attenuation of Lyα photons by neutral hydrogen in the intergalactic medium (IGM) at z ≳ 5 continues to be a powerful probe for studying the epoch of reionization. Given a framework to estimate the intrinsic (true) Lyα emission of high-z sources, one can infer the ionization state of the IGM during reionization. In this work, we use the enlarged XQR-30 sample of 42 high-resolution and high signal-to-noise quasar spectra between $5.8\lesssim \, z\lesssim \, 6.6$ obtained with VLT/X-shooter to place constraints on the IGM neutral fraction. This is achieved using our existing Bayesian QSO reconstruction framework which accounts for uncertainties such as the: (i) posterior distribution of predicted intrinsic Lyα emission profiles (obtained via covariance matrix reconstruction of the Lyα and N v emission lines from unattenuated high-ionization emission line profiles; C iv, Si iv  + O iv], and C iii]) and (ii) distribution of ionized regions within the IGM using synthetic damping wing profiles drawn from a 1.63 Gpc3 reionization simulation. Following careful quality control, we used 23 of the 42 available QSOs to obtain constraints/limits on the IGM neutral fraction during the tail-end of reionization. Our median and 68th percentile constraints on the IGM neutral fraction are: $0.20\substack{+0.14 -0.12}$ and $0.29\substack{+0.14 -0.13}$ at z = 6.15 and 6.35. Further, we also report 68th percentile upper limits of $\bar{x}_{\mathrm{H\, {\small I}}{}} \lt 0.21$, 0.20, 0.21, and 0.18 at z = 5.8, 5.95, 6.05, and 6.55. These results imply reionization is still ongoing at $5.8\lesssim \, z\lesssim \, 6.55$, consistent with previous results from XQR-30 (dark fraction and Lyα forest) along with other observational probes considered in the literature.